Challenges in child and adolescent health across the Arab Gulf countries—Focus on metabolic health - Basma Haris (12040355) (2025)
The Gulf Cooperation Council (GCC) consists of six member states (Bahrain, Kuwait, Oman, Qatar Saudi Arabia and the United Arab Emirates). The combination of an increasing youth population combined with rapid modernisation, increasing per capita income and the paradigm shift towards unhealthy and affluent lifestyles has created a significant burden of non‐communicable diseases (NCDs), especially obesity and diabetes. The aim of this review is to discuss the prevalence of childhood/adolescent obesity and diabetes in the GCC region, which are some of the highest in the world. The review also focuses on the major challenges the GCC region faced in dealing with these lifestyle‐related NCDs. Children and adolescents lack access to specialised professionals for disease management across all healthcare services in the region, with a lack of multidisciplinary teams and support groups. The development of culturally acceptable and community‐based strategies to promote healthy lifestyles at home and in schools will be essential to achieve sustainable change in these countries to reduce the health and economic burden of metabolic health diseases in children and adolescents in the region. Other Information Published in: Clinical Obesity License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/cob.70027